Does It Cost More to Train Residents or to Replace Them? : A Look at the Costs and Benefits of Operating Graduate Medical Education Programs - Barbara O. Wynn, Robert Smalley (RAND Corporation, 2013)
The policy issue underlying this study is whether Medicare support for graduate medical education (GME) should be restructured to differentiate between programs that are less costly or are self-sustaining and those that are more costly to the sponsoring institution and its educational partners. We used available literature, interviews with individuals involved in operating GME programs, and analysis of administrative data to explore how the financial impact of operating residency training programs might differ by specialty. The study does not quantify the variation in financial impact, but it provides a framework for examining both the costs and benefits of operating GME programs to the sponsoring institution and its educational partners. It also identifies the major factors that are likely to affect financial performance and influence program offerings and size. Marginal financial impacts are more likely to influence sponsor decisions on changes in GME program size and offerings and help explain why GME program expansions are occurring without additional Medicare funding. If the hospital has service needs, there is a marginal benefit to adding a resident, particularly in the more-lucrative specialty and subspecialty programs, before considering the additional benefits of any Medicare GME-related revenues.